Towards Rethinking Politics, Policy and Polity in the Anthropocene
LXXIX, 586 p. 79 illus., 71 illus. in color.
Keywords: Humankind faces two anthropogenic threats to its survival that are closely linked. The first is the end of the Holocene and the start of the Anthropocene, which was marked by the test of a nuclear bomb on 16 July 1945. In the prevailing peace and security narrative, nuclear weapons and the ‘other’ (country, bloc or alliance) pose a perceived threat to humankind’s survival. In the Anthropocene narrative, ‘we are the threat’ through our way of life and the burning of hydrocarbons. The start of the Anthropocene coincides with a change in the international order with the setting up of the UN and the Bretton Woods Institutions. Three stages of this order are distinguished: the Cold War (bipolarity), the post-Cold War era (unipolarity), and the end of the rule-based global liberal order (multipolarity) on 24 February 2022. In this book ten multidisciplinary perspectives discuss complexity, Anthropocene geopolitics, peace and security discourses and the German debate on the Anthropocene, planetary boundaries, complex crises and integrative geography in the Anthropocene, governance and politics, and the Patriacene and gender. Both existential threats for humankind are illustrated by cover photos of the first nuclear weapons test on 16 July 1945 and by Category 5 Hurricane Otis, an extreme weather event impacting on Acapulco in Mexico on 25 October 2023. The Anthropocene as a new epoch of Earth history coincides in 1945 with a change in the international order. In the security and peace narrative, the ‘other’ and nuclear weapons pose an existential threat; in the Anthropocene narrative, we are the threat. This dual existential change requires a rethinking of politics, policy and polity. In the social sciences, the Anthropocene is being discussed from multidisciplinary perspectives (geography, political science, and peace, security, and gender studies). This is an open access publication.